Pengaruh Skema Kompensasi dan Religiusitas Terhadap Penilaian Etis Manager atas Investasi Berlebihan Pada CSR - Herman Muliawan; Sany Dwita; Nayang Helmayunita (Universitas Negeri Padang, 2021)
This study aims to examine the effect of pay scheme and religiousity on managers’ ethical judgements in regards to overinvestment in corporate social responsibility. The population in this study were students of the Master Program in the Faculty of Economics, Padang State University. A total of 57 people agreed in this study.Laboratory experiments with a 2 x 2 factorial design were carried out. 57 MM students participate in an experiment. Data analysis was done by using two-way ANOVA. is used at Hypothesis test. The results of this study conclude that pay scheme affects an managers’ ethical judgements in regards to overinvestment in corporate social responsibility with a significance value of the two-way ANOVA analysis test of 0.003<0.05. Religiousity affects an managers’ ethical judgements in regards to overinvestment in corporate social responsibility. The significance value of the two-way ANOVA analysis test was 0.000<0.05.